Pengaruh Profitabilitas, Pertumbuhan Penjualan, Ukuran Perusahaan Terhadap ETR Dengan Leverage Variabel Kontrol - Nada Yolanda; Hilda Mary; Muhammad Fikri Ramadhan (GLOBAL SCIENTS PUBLISHER, 2026)
This study aims to analyze the effect of profitability, sales growth, and company size on the effective tax rate (ETR) with leverage as a control variable in basic and chemical industry companies listed on the Indonesia Stock Exchange (IDX) for the 2020–2024 period. The research sample consisted of 51 companies selected using purposive sampling technique, with data analysis using multiple linear regression through SPSS 23. The results showed that profitability had a significant effect on ETR, while sales growth and company size did not have a significant effect on ETR. Simultaneously, profitability, sales growth, and company size had a significant effect on ETR. Profitability and sales growth with leverage as control variables did not have a significant effect on ETR, while company size with leverage as a control variable had a significant effect. Profitability, sales growth, and company size with leverage as control variables simultaneously had a significant effect on ETR